2002
DOI: 10.1002/ajmg.a.10822
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterization of two (C300F, P425T) arylsulfatase a missense mutations

Abstract: Metachromatic leukodystrophy (OMIM 250100) is a lysosomal storage disease caused by the deficiency of arylsulfatase A (ARSA, EC 3.1.6.8). This disease affects mainly the nervous system, because patients cannot degrade 3-O-sulfo-galactosylceramide (sulfatide), a major myelin lipid. Here we describe the characterization of the biochemical effects of two arylsulfatase A missense mutations, P425T and C300F. Transfection experiments demonstrate the expression of residual ARSA enzyme activity for P425T, but not for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Our results suggest that enzymes have reached a folding state which suffices to pass the ER quality control, when they express at least epitope C partially (Arg370Gln and Arg370Trp). In a separate study we have identified two additional mutations (Phe219Val, Pro425Thr) that generally also fit into this pattern ([11] A Marcão, unpublished data). It should be mentioned that one of these mutations (Phe219Val) was found in a patient with an unusual phenotype and encodes an enzyme that, like Thr274Met, does not react with any of the mAbs.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…Our results suggest that enzymes have reached a folding state which suffices to pass the ER quality control, when they express at least epitope C partially (Arg370Gln and Arg370Trp). In a separate study we have identified two additional mutations (Phe219Val, Pro425Thr) that generally also fit into this pattern ([11] A Marcão, unpublished data). It should be mentioned that one of these mutations (Phe219Val) was found in a patient with an unusual phenotype and encodes an enzyme that, like Thr274Met, does not react with any of the mAbs.…”
Section: Discussionmentioning
confidence: 76%
“…The effects of these mutations have been shown to be rather uniform. Either the amino acid substitutions lead to an arrest of the mutant enzyme in the ER, or the enzyme is degraded in the lysosome after correct sorting [2,9–12]. Here we have investigated wild‐type and mutant ASAs by immunoprecipitation with six structure‐sensitive mAbs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The P425T substitution has recently been shown to be associated with residual enzyme activity. 4 Almost no activity was expressed from the plasmid containing the F219V complementary DNA, whereas low levels of residual activity were found in cells expressing the P425T enzyme (Figure 4). Western blot analysis revealed the presence of ARSA polypeptides in all transfected cells, allowing the conclusion that F219V ARSA has severely reduced specific enzymatic activity (Figure 4, Table).…”
Section: Consequences Of the F219v Substitutionmentioning
confidence: 99%